Performance of a Savonius Turbine with Circular Cylinders Installed in Front of the Convex Blade and Next to the Concave Blade - Shabrina, Dhia Fairuz; Yuwono, Tri Yogi (JMES The International Journal of Mechanical Engineering and Sciences, 2025)
Energy demand is found to be increasing alongside population growth. With fossil energy resources depleting, the necessity for utilizing renewable energy sources, such as wind energy, is recognized. The Savonius wind turbine, characterized by simple construction and the ability to operate at low angular speeds, is noted for its poor efficiency. Circular cylinders were installed to evaluate their impact on turbine performance. Experiments were conducted using two configurations. In the first configuration, a circular cylinder was placed beside the concave blade. In the second configuration, circular cylinders were installed next to the concave blade and in front of the convex blade. Circular cylinders with a diameter of 0.5 times that of the turbine blade were utilized. Wind speeds were varied at 4, 5, 6, and 7 m/s. The coefficients of moment, power, and static torque were obtained. Analysis indicated that the addition of the cylinders in both configurations did not significantly enhance the coefficients of power and moment, but did improve the turbine's ability to self-start. For the turbine with the circular cylinder installed, increasing wind speed resulted in decreasing relative performance compared to the conventional turbine.